Self-directed R&D teams what makes them effective? - Taylor, Glenn L. (Research management (Now: research technology management))
Glenn L. Taylor, Louis J. Snyder, Keith F. Dahnke, and Gary Kuether present the results of a study showing that clear and important goals, good communication and supportive management are key.